Systém odměňování zaměstnanců ve vybrané společnosti a návrh jeho změn - Rollerová, Pavlína (Vysoké učení technické v Brně. Fakulta podnikatelská, 2021)
Diplomová práce je zaměřena na systém odměňování zaměstnanců ve vybrané společnosti. V teoretické části jsou vymezeny základní pojmy z oblasti odměňování zaměstnanců. Analytická část hodnotí současný systém odměňování zaměstnanců ve společnosti, včetně vnitřních a vnějších vlivů působících na daný systém. Na základě provedených analýz jsou navrženy změny současného systému odměňování za účelem zvýšení spokojenosti zaměstnanců.

The master’s thesis is focused on the system of remuneration for employees in the selected company. The theoretical part defines the basic terms of the employee remuneration. The analytical part evaluates the current system of remuneration for employees in the company, including internal and external factors influencing the system. Based on this analysis, changes to the current remuneration system are proposed in order to increase employee satisfaction.
Employee Remuneration System in the Selected Company and Proposal of Changes
Keywords: zaměstnanec; zaměstnavatel; odměňování zaměstnanců; celková odměna; mzda; zaměstnanecké benefity; spokojenost zaměstnanců; employee; employer; remuneration of employees; total remuneration; wage; employee benefits; employee satisfaction